Response of osteoblastic cells to titanium submitted to three different surface treatments Resposta de células osteoblásticas ao titânio submetido a três diferentes tratamentos de superfície - Adriana Soares Santiago; Euler Araújo Santos; Márcia Soares Sader; Marcelo Felippe Santiago; Gloria de Almeida Soares (Sociedade Brasileira de Pesquisa Odontológica, 2005)
In the complex process of bone formation at the implant-tissue interface, surface properties are relevant factors modulating osteoblastic function. In this study, commercially pure titanium (cp Ti) samples were prepared with different surface characteristics using chemical attack with a sulfuric acid/hydrochloric acid based solution (treatment A); chemical attack plus anodic oxidation using phosphoric acid (treatment B); and chemical attack plus thermal oxidation followed by immersion in a sodium fluoride solution (treatment C). The samples were characterized by scanning electron microscopy (SEM), contact profilometry and contact angle. The biological performance of the prepared surfaces was evaluated using mice osteoblastic cell cultures for up to 21 days. Cells seeded on the different titanium samples showed similar behavior during cell attachment and spreading. However, cellular proliferation and differentiation were higher for samples submitted to treatments A and C (p < 0.05; n = 3), which were less rough and showed surface free energy with smaller polar components. No complexo processo de formação óssea na interface implante-osso, as propriedades de superfície são um importante fator modulador da função osteoblástica. No presente estudo, foram preparadas amostras de titânio comercialmente puro (cp Ti) com diferentes propriedades de superfície por meio de ataque químico com solução à base de ácido sulfúrico/clorídrico (tratamento A); ataque químico seguido de oxidação anódica com ácido fosfórico (tratamento B); e ataque químico seguido de oxidação térmica e imersão em fluoreto de sódio (tratamento C). As chapas foram caracterizadas por meio de microscopia eletrônica de varredura (MEV), perfilometria e ângulo de contato. O comportamento de células osteoblásticas de camundongo foi acompanhado por três semanas. As células cultivadas sobre os diferentes substratos de titânio apresentaram um modelo de comportamento similar durante as etapas de adesão e espalhamento. No entanto, a proliferação e a diferenciação celulares foram maiores nas amostras submetidas aos tratamentos A e C, que se apresentaram menos rugosas e com energia livre de superfície com menores componentes polares.